ZPAC is required for normal spermatogenesis in mice. Issue 10 (6th July 2015) - Zuo, Er‐Wei; Yang, Xiao‐Gan; Lu, Yang‐Qing; Xie, Long; Shang, Jiang‐Hua; Li, Di; Yang, Huan; Hu, Lin‐Lin; Zhao, Hui‐Min; Lu, Sheng‐Sheng; Lu, Ke‐Huan
SUMMARY The ubiquitin‐proteasome pathway, involved in genetic recombination and sex‐chromosome silencing during meiosis, plays critical roles in the specification of germ‐line stem cells and the differentiation of gametes from gonocytes. Zygote‐specific proteasome assembly chaperone (ZPAC) is expressed in the early mouse embryo, where it is important for progression of the mouse maternal‐to‐zygotic transition. The role of ZPAC during spermatogenesis in the adult gonads, however, remains unknown. In this study, rapid amplification of cDNA ends was used to determine the Zpac cDNA sequence, a 1584‐bp transcript that includes a putative 1122‐bp open reading frame coding for a 373 amino acid protein. Western blot and immunohistochemistry revealed that ZPAC was specifically expressed in gonads. To further dissect the function of ZPAC during spermatogenesis, we employed PiggyBac‐based RNA interference vectors for transgenesis combined with cell transplantation to deplete Zpac during spermatogenesis. This RNAi‐mediate depletion in Zpac expression disrupted normal spermatogenesis from spermatogonial stem cells. Two independent yeast two‐hybrid screens further revealed an interaction between ZPAC and SYCE1. Together, these data suggest that ZPAC is required for normal spermatogenesis in mice. Mol. Reprod. Dev. 82: 747–755, 2015. © 2015 Wiley Periodicals, Inc.